miR-31-3p functions as a tumor suppressor by directly targeting GABBR2 in prostate cancer - Choi, Sujin; Lee, Soonchul; Han, Young-Hoon; Choi, Junwon; Kim, Isaac; Lee, Jusung; An, Hyun-Ju (Frontiers in Oncology, 2022)
MicroRNAs are key regulators of gene expression in tumorigenesis. In this study, we investigated the tumor-suppressive function of miR-31-3p. Analysis of the Gene Expression Omnibus database revealed that the expression of miR-31-3p in prostate cancer (PC) tissues were lower than that in adjacent normal tissues from patients with PC. miR-31-3p induced apoptosis in PC cells. Transfection with miR-31-3p significantly decreased cell proliferation, migration, invasiveness, and tumor sphere-forming ability, as determined using the cell counting kit-8, transwell, and sphere-forming assays. GABBR2 was the direct target of miR-31-3p. Intratumoral injection of a miR-31-3p mimic suppressed tumor growth in a mouse with DU145 xenograft. These results suggested that miR-31-3p performs a novel tumor-suppressive function in PC and may be used for the development of anticancer miRNA therapeutics.